Financial Bootstrapping Strategies in an Indonesian Edutech Startup: Transitioning from Non-Profit to Profit Orientation - Syauqi Amani; Sutrisno; Zaenal Arifin (Cita konsultindo, 2026)
This study Analyses the business performance and financial structure dynamics of Neuversity, an Edutech entity in Yogyakarta, Indonesia, during its strategic transition from a non-profit foundation (Yayasan) to a profit-oriented corporation (PT). The research evaluates the effectiveness of financial bootstrapping strategies in maintaining sustainability after the cessation of external grant funding. Method: Using a descriptive quantitative approach with a case study method, this research nalyses financial data from the third quarter (Q3) of 2025. The study focuses on Working Capital Management and Spontaneous Financing ratios. Results: The findings indicate that the company successfully pivoted to a B2B model. However, regarding Working Capital Management, the company faces liquidity constraints despite high profits, evidenced by a low Collection Rate of 44.5%. Conversely, the Financial Bootstrapping strategy proved effective, evidenced by an 18.1% ratio of spontaneous financing to total assets and a 56.6% cost reduction during low-revenue periods. Conclusion: While financial bootstrapping successfully secured operational sustainability without interest-bearing debt, long-term stability requires stricter liquidity discipline through better Working Capital Management.